Contratos agrários na agroindústria canavieira em Goiás:legalidades e conflitos - PICANÇO FILHO, Artêmio Ferreira (2010)
With the retake of the agro-energetic policies, the Central Government in Brazil was forced to present public policies to stimulate the expansion of the sugarcane agribusiness in the nation. The agroindustrial sector related to the production of juices and sugarcane derivatives in the Goiás state, experiencing a time of great expansion due to the construction of new industrial unities, opened possibilities for the participation of new segments of the society -sugarcane suppliers and landlords- in the sugarcane agroindustrial complex via rental contracts for available lands and contracts for the supply of raw material. This research was carried out via a qualitative approach and was based upon a range of methodological procedures literature research, documental research, and interviews to obtain the dataset. Since the 1930 s the Brazilian Central Government has stated laws to regulate and to discipline the contractual relationship dealt amongst the social segments involved in the sugarcane agribusiness with the purpose to promote the development of the productive segment of the country s industry, and to establish patterns for social behaviour in accordance with a rational bureaucratic administration. The conclusion is that the agrarian contracts dealt amongst the different social segments involved in the sugarcane industry, although founded upon legal apparatus, did not guarantee the farmers right, or even it did minimize the conflicts amongst the involved agents in this sector of the economy. The agroindustry holds the power of the information which generates asymmetry in the social relationship established in the agrarian contracts. From their side, the farmers landrenters or sugarcane suppliers , comply with the impositions from the sugarcane agroindustry, and continue linked to it because of the lack of better options of economic insertion.